Transformation of the rural nonfarm economy during rapid urbanization and structural transformation in developing regions - Hazell, Peter B. R.; Haggblade, Steven; Reardon, Thomas (Annual Reviews, 2024)
This article reviews the past 25 years of empirical research on the rural nonfarm economy (RNFE) in developing countries; that literature has evolved in ways that track and mirror the rural transformation itself. Since 2000, rapid urbanization, structural transformation, and a sharp series of economic, climate, and disease shocks have influenced trajectories in the RNFE. It has grown to become, on average, the predominant source of income for rural households in developing countries. Both segments of the RNFE—activities linked to agricultural value chains as well as those unrelated to the agricultural sector—have grown. Understanding how each component of the RNFE influences rural incomes, employment, resilience, women, youth, and farming and natural resource management practices is, therefore, more important than ever.